Aqueous spice extracts as alternative antimycotics to control highly drug resistant extensive biofilm forming clinical isolates of Candida albicans. - Bindu Sadanandan; Vaniyamparambath Vijayalakshmi; Priya Ashrit; Uddagiri Venkanna Babu; Lakavalli Mohan Sharath Kumar; Vasulingam Sampath; Kalidas Shetty; Amruta Purushottam Joglekar; Rashmi Awaknavar (PLoS ONE)
Candida albicans form biofilm by associating with biotic and abiotic surfaces. Biofilm formation by C. albicans is relevant and significant as the organisms residing within, gain resistance to conventional antimycotics and are therefore difficult to treat. This study targeted the potential of spice-based antimycotics to control C. albicans biofilms. Ten clinical isolates of C. albicans along with a standard culture MTCC-3017 (ATCC-90028) were screened for their biofilm-forming ability. C. albicans M-207 and C. albicans S-470 were identified as high biofilm formers by point inoculation on Trypticase Soy Agar (TSA) medium as they formed a lawn within 16 h and exhibited resistance to fluconazole and caspofungin at 25 mcg and 8 mcg respectively. Aqueous and organic spice extracts were screened for their antimycotic activity against C. albicans M-207 and S-470 by agar and disc diffusion and a Zone of Inhibition was observed. Minimal Inhibitory Concentration was determined based on growth absorbance and cell viability measurements. The whole aqueous extract of garlic inhibited biofilms of C. albicans M-207, whereas whole aqueous extracts of garlic, clove, and Indian gooseberry were effective in controlling C. albicans S-470 biofilm within 12 h of incubation. The presence of allicin, ellagic acid, and gallic acid as dominant compounds in the aqueous extracts of garlic, clove, and Indian gooseberry respectively was determined by High-Performance Thin Layer Chromatography and Liquid Chromatography-Mass Spectrometry. The morphology of C. albicans biofilm at different growth periods was also determined through bright field microscopy, phase contrast microscopy, and fluorescence microscopy. The results of this study indicated that the alternate approach in controlling high biofilm-forming, multi-drug resistant clinical isolates of C. albicans M-207 and S-470 using whole aqueous extracts of garlic, clove, and Indian gooseberry is a safe, potential, and cost-effective one that can benefit the health care needs with additional effective therapeutics to treat biofilm infections.